Improvement Of Molecular Methods For Detection Of Pathogenic Escherichia Coli. - Abdullah Al-Haj, Nagi Ahmed (2007)
Diarrhea is one of the leading causes of illnesses and death among children in developing countries, where an estimated 1.3 billion episodes and 4 to 10 million deaths occur each year in children below 5 years of age. The common pathogens of diarrhea are diarrheagenic Escherichia coli (DEC), Group A rotavirus, Shigella spp, Salmonella spp, Campylobacter, and Vibrio cholerae. Microbiological insights including phenotypic and genotypic characterisation are valuable approaches with application in management and prevention of diarrheal outbreaks by E. coli. In the present study, the Random Amplified polymorphic DNA (RAPD) fingerprinting technique allowed genetic diversity assessment of 25 E. coli isolates. Six out of 20 arbitrary primers namely, OPAE 4, 9, 10, 11, 12 and 18 produced DNA fingerprinting patterns providing the discriminatory power and the display of the potential epidemiological and diagnostic markers. A highly significant finding from the DNA fingerprinting is the display of a predominant band at a size of 308 bp when arbitrary